2018
DOI: 10.1158/0008-5472.can-17-1900
|View full text |Cite
|
Sign up to set email alerts
|

Germline Lysine-Specific Demethylase 1 (LSD1/KDM1A) Mutations Confer Susceptibility to Multiple Myeloma

Abstract: Given the frequent and largely incurable occurrence of multiple myeloma, identification of germline genetic mutations that predispose cells to multiple myeloma may provide insight into disease etiology and the developmental mechanisms of its cell of origin, the plasma cell (PC). Here, we identified familial and early-onset multiple myeloma kindreds with truncating mutations in lysine-specific demethylase 1 (LSD1/KDM1A), an epigenetic transcriptional repressor that primarily demethylates histone H3 on lysine 4 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 51 publications
0
52
0
Order By: Relevance
“… 22 In addition, there have been recently described autosomal germline mutations that can predispose a patient to MM. 23 At least some of the differences in incidence may be due to lack of diagnostic abilities in lower SDI countries compared with high SDI countries and do not necessarily reflect differences in disease biology (eFigure 6 in the Supplement shows a map of the SDI quintiles). Supporting this hypothesis is the fact that the disease burden of MM in African Americans in the United States is markedly higher than that of European Americans in the United States, yet the disease burden among Africans living in Africa is among the lowest in the world, as shown in our study and in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“… 22 In addition, there have been recently described autosomal germline mutations that can predispose a patient to MM. 23 At least some of the differences in incidence may be due to lack of diagnostic abilities in lower SDI countries compared with high SDI countries and do not necessarily reflect differences in disease biology (eFigure 6 in the Supplement shows a map of the SDI quintiles). Supporting this hypothesis is the fact that the disease burden of MM in African Americans in the United States is markedly higher than that of European Americans in the United States, yet the disease burden among Africans living in Africa is among the lowest in the world, as shown in our study and in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, cytogenetic changes such as hyperdiploidy or translocations involving recurrent oncogenes and the immunoglobulin heavy chain locus are considered initiating events (4). In some individuals, inherited alleles (i.e., germline polymorphisms) can increase the risk of developing MM but this is considered a rare occurrence and all alleles identified so far have been shown to only confer a small risk (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). On the contrary, gene mutations are frequent in newly diagnosed MM (NDMM) and have been particularly characterized since the advent of next generation sequencing (NGS) technologies (15)(16)(17)(18)(19)(20)(21)(22).…”
Section: Molecular Pathogenesis Of Multiple Myeloma and Related Monocmentioning
confidence: 99%
“…Exposure to farm work, printing and cleaning occupations appear to have some association with an increased risk of MM [19,20]. Some studies have identified numerous predisposing genetic factors for MM [21][22][23]. However, as yet, the role of these exposures and the distribution of genetic susceptibility among different population groups have not been evaluated.…”
Section: Discussionmentioning
confidence: 99%